Islamic bank stability and efficiency: A cross-country analysis - Fakhrunnas, Faaza; Boubechtoula, Younes; Nahda, Katiya; Rezoanul Hoque, Mohammad (Economic Journal of Emerging Markets, 2024)
Purpose ― The study investigates the impact of the efficiency of Islamic banks on banking stability. Method ― A panel data analysis using the Least Square Dummy Variable Corrected (LSDVC) method is employed to examine the impact of efficiency on banking stability in Islamic banks. The study has a sample of 54 Islamic banks across eight countries from 2013 to 2021.Findings ― The findings reveal that the efficiency of Islamic banks has a positive and significant effect on banking stability. In addition, financial turmoil negatively and significantly affects the stability of Islamic banks but does not significantly affect institutional development. Additionally, financial turmoil can influence how effectively Islamic banks manage their businesses in response to banking stability. The outcomes are robust across various robustness methods. Implications ― The results imply that the efficiency of Islamic banks has a pivotal role in banking stability, considering the efficiency level. To ensure the stability of Islamic banks, practitioners and regulators of Islamic banks have to achieve and maintain the efficiency of Islamic banks by implementing the required policies and guidelines.Originality/Value ― Previous studies examining the impact of Islamic banks' efficiency on banking stability remain limited. The paper fills the research gap by examining how Islamic bank efficiency affects banking stability, considering the effects of financial turmoil and institutional development.